Crystallisation of the amorphous ices in the intermediate pressure regime - J. Stern (Nature Portfolio, 2017)
Abstract The crystallisation behaviour of very high-density amorphous ice (VHDA) and unannealed high-density amorphous ice (uHDA) has been studied in situ by volumetry and ex situ by powder x-ray diffraction in the intermediate pressure range 0.7–1.8 GPa employing different heating rates (0.5, 5 and 30 K min−1). This study shows that at pressures >1 GPa the crystallisation behaviour of VHDA and uHDA is basically the same for all heating rates. That is, parallel crystallisation is almost entirely suppressed with mainly ice XII forming. This contrasts former results reporting parallel crystallisation to approximately levelled phase mixtures of ice IV and ice XII even at higher pressures for uHDA. We speculate this to be due to formation of microcracks upon decompression in earlier works, but not in the present one. Crystallisation temperatures T x are up to 16 K higher than previously reported, raising the low-temperature border to no man’s land and opening a considerably larger window for future studies on non-crystalline water. The results indicate uHDA to contain heterogeneities on the nanoscale, but VHDA to be rather homogeneous with nano-crystallites being largely absent. Upon transforming uHDA to VHDA, the nano-scale heterogeneities disappear for >1 GPa whereas microcracks do not.